Effectiveness of the Manori Sapuka Community-Based Adherence Program on Blood Pressure Control Among Hypertensive Patients - Faisal, Faisal; Anto, Ambo; Ibrahim, Muhammad Indra (Chakra Brahmanda Lentera Institute, 2026)
Background: Hypertension is a chronic disease often referred to as a